DETEKSI DINI PERTUMBUHAN DAN PERKEMBANGAN ANAK USIA PRASEKOLAH DI TK NEGERI PEMBINA PARE KEDIRI - Sulistyorini, Ariani; Sunaringtyas, Widyasih; Setiawan, Lilik (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Children are an important national asset for the future of life. Children can fail to get what their parents expect if the child experiences a disturbance during their growth and development. Children will grow and develop according to their stages. This community service aims to carry out early detection of the growth and development of preschool-age children. The method for community service is education and intervention to examine children's growth and development using the DDST examination instrument and KPSP format for 53 preschool-aged children. The implementation time is 14-20 December 2023 at the Pembina Pare State Kindergarten, Kediri. The results of examinations from 53 students regarding early detection of children's growth and development showed that 50 children (94%) had normal body weight, 41 children (77%) had normal TB, and 42 children (79%) had good/normal nutrition. For development, the results showed that 52 children (98%) were normal.  Comprehensive and coordinated early detection and intervention of deviations in toddler growth and development carried out in the form of a partnership between family, community, and professional staff will improve the quality of early childhood growth and development and readiness to enter formal education. Actions that can be given are to praise parents about the successes that have been achieved, encourage them to continue stimulation according to age, and schedule the next visit.